Prosthetic Rehabilitation of Maxillectomy Patient with Post-Surgical Obturator: A Case Report - Mishra, Meena Kumari; Singh, Raj Kumar; Suwal, Pramita; Parajuli, Prakash Kumar; Shrestha, Pragya; Shakya, Rojina (Journal of College of Medical Sciences-Nepal, 2015)
Case description: A 60 year old female patient presented to Department of Prosthodontics, CODS, BPKIHS, Dharan with a chief complain of loose obturator. History revealed that patient had undergone partial maxillectomy for squamous cell carcinoma 7 years back. The patient also has been wearing obturator which was loose when the patient reported to the department. On examination, the site of surgery was the maxillary right buccal sulcus area and a part of the hard palate including teeth number 11, 12, 13, 14, 15, 16, 17. The presented defect situation corresponded to a Class I situation (resection performed along the palatalmidline) according to the Aramany classification of defects. The surgical site showed complete healing. A hollow-bulb obturator was fabricated for rehabilitation of the defect. Conclusion: The extensive surgical procedures necessary to eradicate cancer of the head and neck and to prevent local recurrence or regional metastasis often leave extremely large physical defects which present almost insurmountable surgical difficulties in restoring acceptable function or esthetics. The prosthesis rehabilitated the patient in terms of function by providing better masticatory efficiency, phonetics by adding resonance to the voice, hence improving the clarity of speech and also improved the esthetics of the patient. JCMS Nepal 2014; 10(4):32-36